Preparing and Evaluating the Effectiveness of the Creative Educational Program on Spiritual Happiness, Creative Thinking and Problem-Solving Skills in University Students in Mashad - effat rassouli saniabadi; Gholam Ali Afrooz; Fereydoon Yaryari; Masood Lavasani (مطالعات روانشناسی تربیتی)
The purpose of this study is to develop and evaluate the effectiveness of creative education program on spiritual vitality, creative thinking and problem solving skills in university students. Based on applied-experimental research of pre-test-post-test with control group and implementation of tests for measuring Abedi creativity (CT), Afrooz spiritual vitality (SHS) and Basador bproblem-solving skills (CPS), the necessary information on the components of creative thinking (fluid, Expansion, flexibility, and initiative ) ,spiritual vitality (feelings, behaviors, and beliefs) and problem-solving skills were collected. The study sample consisted of 72 students at the undergraduate level who were selected by multi-stage random sampling method from different faculties of humanities of Mashhad universities. After 10 sessions of sessions related to creative teaching techniques of Triz, scamper and brainstorming with subjects in experimental groups and data analysis by multivariate analysis of covariance and analysis of covariance (SPSS software version 22), the results showed that Creative education program has a positive effect on spiritual vitality, creative thinking skills and problem solving skills of students, so that the effect was 53.2% according to the ETA coefficient squared. The findings also showed that fluid skill in the experimental group was not significantly higher than the control group. The results also showed that there is no difference between male and female students in terms of the effectiveness of the creative education program.